Analisis Perspektif Masyarakat Terhadap Cerai Gugat Di Kabupaten Bekasi - Fairuz Khairunniesa; Amirudin; Iqbal Amar Muzaki (Asy-Syari’ah : Jurnal Hukum Islam, 2022)
Divorce is the end of a marriage with the severance of the relationship between husband and wife due to the failure to carry out their respective roles in fostering a household. In the view of the community that divorce is a way out of household problems that must be avoided because it is a disgrace to the family. The purpose of writing this article is to analyze the community's perspective on the phenomenon of divorce and lawsuits that often occur in the community. The writing of this article uses a qualitative approach, case study method with data collection through interviews with informants, literature review, and documentation. The results of the study show that the perspective of the people who are respondents in this study is related to the case of litigation that occurs in the community, something that is not good and the result of the divorce is that there will be divisions in the family. In the view of society, a woman must carry out her obligations as a wife and according to her nature to create a harmonious family, as well as a husband who must carry out his obligations as the head of the household, because marriage must be maintained in order to maintain harmony and maintain its sacredness.